Three-color vector nematicon - Laudyn, Urszula Anna; Kwaśny, Michał; Karpierz, Mirosław; Assanto, Gaetano (Photonics Letters of Poland, 2017)
Light localization via reorientation in nematic liquid crystals supports multi-component optical spatial solitons, i.e., vector nematicons. By launching three optical beams of different wavelengths and the same input polarization in a bias-free planar cell, we demonstrate a three-color vector nematicon which is self-trapped thanks to its incoherent nature. Full Text: PDF References G. I. Stegeman and M. Segev, "Optical Spatial Solitons and Their Interactions: Universality and Diversity", Science 286 (5444), 1518 (1999) CrossRef W. Królikowski and O. Bang, "Solitons in nonlocal nonlinear media: Exact solutions", Phys. Rev. E 63, 016610 (2000) CrossRef D. Suter and T. Blasberg, "Stabilization of transverse solitary waves by a nonlocal response of the nonlinear medium", Phys. Rev. A 48, 4583 (1993) CrossRef G. Assanto and M. Peccianti, "Spatial solitons in nematic liquid crystals", IEEE J. Quantum Electron. 39 (1), 13 (2003). CrossRef G. Assanto and M. Karpierz, "Nematicons: self-localised beams in nematic liquid crystals", Liq. Cryst. 36 (10), 1161 (2009) CrossRef M. Peccianti and G. Assanto, "Nematicons", Phys. Rep. 516, 147 (2012). CrossRef M. Peccianti and G. Assanto, "Incoherent spatial solitary waves in nematic liquid crystals", Opt. Lett. 26 (22), 1791 (2001) CrossRef M. Peccianti and G. Assanto, "Nematic liquid crystals: A suitable medium for self-confinement of coherent and incoherent light", Phys. Rev. E Rap. Commun. 65, 035603 (2002) CrossRef G. Assanto, M. Peccianti, C. Umeton, A. De Luca and I. C. Khoo, "Coherent and Incoherent Spatial Solitons in Bulk Nematic Liquid Crystals", Mol. Cryst. Liq. Cryst. 375, 617 (2002) CrossRef A. Alberucci, M. Peccianti, G. Assanto, A. Dyadyusha and M. Kaczmarek, "Two-Color Vector Solitons In Nonlocal Media", Phys. Rev. Lett. 97, 153903 (2006) CrossRef G. Assanto, N. F. Smyth and A. L. Worthy, "Two-color, nonlocal vector solitary waves with angular momentum in nematic liquid crystals", Phys. Rev. A 78 (1), 013832 (2008) CrossRef G. Assanto, K. Garcia-Reimbert, A. A. Minzoni, N. F. Smyth and A. Worthy, "Lagrange solution for three wavelength solitary wave clusters in nematic liquid crystals", Physica D 240, 1213 (2011) CrossRef G. Assanto, A. A. Minzoni and N. F. Smyth, "Vortex confinement and bending with nonlocal solitons", Opt. Lett. 39 (3), 509 (2014) CrossRef G. Assanto, A. A. Minzoni and N. F. Smyth, "Deflection of nematicon-vortex vector solitons in liquid crystals", Phys. Rev. A 89, 013827 (2014) CrossRef G. Assanto and N. F. Smyth, "Soliton Aided Propagation and Routing of Vortex Beams in Nonlocal Media", J. Las. Opt. Photon. 1, 105 (2014) CrossRef Y. V. Izdebskaya, G. Assanto and W. Krolikowski, "Observation of stable-vector vortex solitons", Opt. Lett. 40 (17), 4182 (2015) CrossRef Y. V. Izdebskaya, W. Krolikowski, N. F. Smyth and G. Assanto, "Vortex stabilization by means of spatial solitons in nonlocal media", J. Opt. 18 (5), 054006 (2016) CrossRef J. F. Henninot, J. Blach and M. Warenghem, "Experimental study of the nonlocality of spatial optical solitons excited in nematic liquid crystal", J. Opt. A 9, 20 (2007) CrossRef Y. V. Izdebskaya, V. G. Shvedov, A. S. Desyatnikov, W. Z. Krolikowski, M. Belic, G. Assanto and Y. S. Kivshar, "Counterpropagating nematicons in bias-free liquid crystals", Opt. Express 18 (4), 3258 (2010) CrossRef N. Karimi, A. Alberucci, M. Virkki, M. Kauranen and G. Assanto, "Phase-front curvature effects on nematicon generation", J. Opt. Soc. Am. B 5 (33), 903 (2016) CrossRef P. G. de Gennes and J. Prost, The Physics of Liquid Crystals, Oxford Science Publications (Clarendon Press, 2nd edition, 1993) I. C. Khoo, Liquid Crystals: Physical Properties and Nonlinear Optical Phenomena (Wiley, New York, 1995) A. Piccardi, M. Trotta, M. Kwasny, A. Alberucci, R. Asquini, M. Karpierz, A. d’Alessandro and G. Assanto, "Trends and trade-offs in nematicon propagation", Appl. Phys. B 104 (4), 805 (2011) CrossRef M. Kwasny, U. A. Laudyn, F. A. Sala, A. Alberucci, M. A. Karpierz and G. Assanto, "Self-guided beams in low-birefringence nematic liquid crystals", Phys. Rev. A 86 (1), 01382 (2012) CrossRef M. Peccianti, A. Fratalocchi and G. Assanto, "Transverse dynamics of nematicons", Opt. Express 12 (26), 6524 (2004) CrossRef C. Conti, M. Peccianti and G. Assanto, "Observation of Optical Spatial Solitons in a Highly Nonlocal Medium", Phys. Rev. Lett. 92 (11), 113902 (2004) CrossRef A. Alberucci, C.-P. Jisha and G. Assanto, "Breather solitons in highly nonlocal media", J. Opt. 18, 125501 (2016) CrossRef